PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI - Dewi, Ni Wayan Ratna; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The purpose of this study is to understand the influence of region original revenue, general fund allocation, specific fund allocation, capital expenditure to economic growth. The population in this study were eight counties and one city in Bali during the period of 2010 – 2014 and using saturation sampling methods. The data used in this research is secondary data obtained from the document of Badan Pusat Statistik of Bali Province, the budget realization report and GDRP at constant prices. The analytical method used multiple linear regression analysis. The results show that region original revenue and specific fund allocation has negative effects on the economic growth; general fund allocation and capital expenditure has no effects on the economic growth.
Keywords: Region Original Revenue; General Fund Allocation; Specific Fund Allocation; Capital Expenditure; and Economic Growth